Pengaruh Kompensasi Terhadap Motivasi Kerja Karyawan - Lukman Lukman; Syifa Musdhalifah Arsyad; Ihdina Sazalia Rahmah; Adliana Adliana; Adya Amalyah Putri (CV. ULIL ALBAB CORP, 2024)
This research aims to find out whether compensation can increase work motivation in employees. This research was conducted on employees at PT. Mandala Multifinance, Tbk, Makassar 1 and Makassar 2 branches. The sample in this study was 40 respondents with the sampling technique used, namely purposive sampling. The data collection method in this research uses a Likert scale with two variables, namely motivation and compensation. The research results show that there is a significant positive influence between financial compensation and work motivation.